The effect of institutional ownership, managerial ownership, free cash flow, firm size and corporate growth on debt policy - Laili Ayu Safitri; Putri Wulanditya (STIE Perbanas Surabaya, 2017)
Debt policy is a decision made by a company to obtain funds from outside parties to meet the operational needs of the company. Recent economic development encourages compa-nies to continue to expand their business in order to survive and gain better corporate value. To develop the business, a company needs more funds. And when the funds are not enough, the company will perform debt policy. However, debt policy can be risky and therefore the company should carry out operational activities effectively in order to avoid the risks. This study aims to determine the effect of institutional ownership, managerial ownership, profitability, free cash flow, firm size and corporate growth on debt policy. The data used in this study are secondary data, that is, the financial reports of mining sector companies listed on the Indonesia Stock Exchange 2011-2015. The research is using purposive sampling method consisting of 59 data. Analysis techniques used in this study are classical assumptions and multiple regression analysis. The results show that institutional ownership and profitability have negative effect on debt policy, and free cash flow has positive effect on debt policy, while, managerial ownership, firm size, and corpo-rate growth have no effect on debt policy. The implication of this study is for investors to notice that the debt policy taken by mining companies is influenced by the number of shares owned by the institution, return on equity, and the amount of free cash flow.